2011
DOI: 10.1007/s00228-011-1163-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of alprazolam (a marker of CYP3A4) in hemodialysis patients with persistent inflammation

Abstract: The correlation between CYP3A4 activity (assessed by alprazolam 4-hydroxylation) and CRP level suggests that inflammation may downregulate CYP3A4 activity. If confirmed, this could have major implications for drug dosing in persistently inflamed patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…In a small (n = 26) recent study in patients with end-stage renal disease, an association between inflammation (increased CRP) and low CYP3A4 activity assessed by alprazolam 4-hydroxylation was noted, but there was no correlation between inflammation and 4b-hydroxycholesterol (Molanaei et al, 2012). Alprazolam 4-hydroxylation is a marker for rapid changes in CYP3A4 activity, whereas 4b-hydroxycholesterol reflects CYP3A4 activity over longer time periods and is more useful in determining induction than inhibition of CYP3A4.…”
Section: Downloaded Frommentioning
confidence: 91%
See 1 more Smart Citation
“…In a small (n = 26) recent study in patients with end-stage renal disease, an association between inflammation (increased CRP) and low CYP3A4 activity assessed by alprazolam 4-hydroxylation was noted, but there was no correlation between inflammation and 4b-hydroxycholesterol (Molanaei et al, 2012). Alprazolam 4-hydroxylation is a marker for rapid changes in CYP3A4 activity, whereas 4b-hydroxycholesterol reflects CYP3A4 activity over longer time periods and is more useful in determining induction than inhibition of CYP3A4.…”
Section: Downloaded Frommentioning
confidence: 91%
“…Furthermore, this study material included patients with high frequency of infections, offering an opportunity to study whether acute inflammation, measured as C-reactive protein (CRP), impacts on the CYP3A biomarker. It was previously shown in cell and animal experiments that infections and inflammation can downregulate CYP3A4 expression (Morgan et al, 2008;Morgan, 2009), and a recent study in hemodialysis patients indicated a correlation between CYP3A4-dependent alprazolam 4-hydroxylation and CRP (Molanaei et al, 2012).…”
Section: Introductionmentioning
confidence: 95%
“…In addition, in CKD patients, mitigation of CYPmediated drug metabolism is shown, 113,114 including changes in bupropion, alprazolam, and fexofenadine pharmacokinetics. [115][116][117] Moreover, is has been shown both in vitro and in vivo that hemodialysis improves functional expression of hepatic CYP3A4, 118,119 implicating a role for uremic toxins in altering drug metabolism in CKD patients. This notion is supported by the study from Sun et al, 120 which showed that indoxyl sulfate and CMPF reduced erythromycin metabolism by CYP3A in rat liver microsomes.…”
Section: Intracellular Fate Of Uremic Toxinsmentioning
confidence: 99%
“…A study on the effect of persistent inflammation in patients with renal failure and who were undergoing hemodialysis on the pharmacokinetics of alprazolam, a CYP3A4 substrate, revealed that after a single dose of alprazolam, there was a significant correlation between CYP3A4 activity and CRP level, which suggested that inflammation may clinically down-regulate CYP3A4 activity (Molanaei et al, 2012). Studies in human liver microsomes have shown that oxatomide, an H1-antihistamine, is mainly metabolized by CYP3A4 and CYP2D6, and there has been a report of severe long-lasting impaired consciousness induced by therapeutic doses of oxatomide in a child affected by acute gastroenteritis (Antoniazzi et al, 2012).…”
Section: Evidence For Potential Phenoconversion Of Dmes In Other Inflmentioning
confidence: 99%